Isotretinoin treatment of autosomal recessive congenital ichthyosis complicated by coexisting dysferlinopathy. (1st June 2016) - Mashiah, J.; Harel, A.; Bitterman, O.; Sagi, L.; Gat, A.; Fellig, Y.; Ben‐Shachar, S.; Sprecher, E.
Summary: Consanguinity is known to be associated with an increase in the prevalence of autosomal recessive disorders such as autosomal recessive congenital ichthyosis (ARCI). ARCI often responds well to retinoid treatment. We describe a patient with ARCI who improved under isotretinoin treatment. The patient subsequently developed elevated levels of serum creatinine phosphokinase (CPK), which led to the diagnosis of a second autosomal recessive disorder, dysferlinopathy, a rare myopathy characterized by muscle weakness, decreased tendon reflexes and marked elevation of CPK levels. This report demonstrates the need for physicians to remain alert to the possible coexistence of rare and mutually relevant disorders in populations with a high rate of consanguinity.